2008
DOI: 10.2165/00044011-200828080-00004
|View full text |Cite
|
Sign up to set email alerts
|

Thioctic Acid and Acetyl-L-Carnitine in the Treatment of Sciatic Pain Caused by a Herniated Disc

Abstract: Thioctic acid 600 mg/day appears to be at least as effective as ALC in the treatment of sciatic pain caused by a herniated disc and may be associated with an improvement in symptom scores and reduced need for analgesia. However, because of the limited number of patients evaluated and the lack of a placebo control in this trial, further studies are warranted in order to provide more definitive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 17 publications
1
31
0
1
Order By: Relevance
“…Three studies 161,172,226 did not report any pain, global or CSOM data. 161,172,226 Fifteen studies compared different types of non-opioids 223,227,229,[231][232][233][234][235][236][237][238][239][240][241] (seven of which were three-arm studies 57,215,223,227,229 and two studies of which were reported in a single publication 223 ). The types of non-opioids being compared are presented in Table 45b but the findings are not considered further.…”
Section: Description Of Non-opioids Studiesmentioning
confidence: 99%
“…Three studies 161,172,226 did not report any pain, global or CSOM data. 161,172,226 Fifteen studies compared different types of non-opioids 223,227,229,[231][232][233][234][235][236][237][238][239][240][241] (seven of which were three-arm studies 57,215,223,227,229 and two studies of which were reported in a single publication 223 ). The types of non-opioids being compared are presented in Table 45b but the findings are not considered further.…”
Section: Description Of Non-opioids Studiesmentioning
confidence: 99%
“…LA and DHLA are important in the citric-acid cycle and in energy metabolism; in addition, they function as scavengers of free radicals and readily participate in redox reactions that modulate thiol groups in proteins (58). Human and animal studies have clearly documented analgesic properties of LA; however, molecular mechanisms underlying the analgesic properties of LA initially were not understood (7,39). Lee et al (32) used Ca V 3.2 knockout mice to examine molecular determinants of LA inhibition of T-current in DRG cells and in vivo pain responses.…”
Section: Molecular Mechanisms Of Modulation Of Ca V 32 T-current By mentioning
confidence: 99%
“…ALC is known to affect the activity of enzymes involved in the energy turnover, thus modulating either different neurotransmitter systems (Picconi et al, 2006;Tolu et al, 2002) or intracellular pathways (Galeotti et al, 2004;Pérez-De La Cruz et al, 2008). A relevant action ascribed to ALC is its anti-nociceptive effect observed in the treatment of painful neuropathies of various origins (Chiechio et al, 2010;Di Cesare Mannelli et al, 2009;Janiri et al, 2009;Memeo and Loiero, 2008;Sima, 2007;Sima et al, 2005). In addition, there is evidence that ALC improves cognitive capabilities (Adriani et al, 2004;Ando et al, 2001;Marini et al, 2006;Shea, 2007).…”
Section: Introductionmentioning
confidence: 99%